Efek Antibakterisid Madu terhadap Escherichia coli - Samapta, Alghazali; Sagiran, - (Universitas Muhammadiyah Yogyakarta, 2003)
Allah Azza Wa J alia said in Quran, â€œFrom inside a beeâ€™s stomach it is spread off a colourful drink, which consists of medicine that may cure human diseases. (QS. 16:69). The term of â€œBack to Natureâ€, brings us to go back to nature, lets human to see alternative medicine besides the conventional medi-cine. There are some limitations of conventional antibiotic, i.e. causing bacteÂ¬ria resistence and side effects in quite a lot cases. This is much different with â€œhoneyâ€, which posseses some superiorities such as easy administration, good absorption, minimal side effects and affordable price of medicine. The antibacterial activity of honey can be used as an alternative antibac-terial remedy which is more superior and has minimal side effect. In Islam, honey is a nutrition, food supplement and a medicine as well. The objective of this research was to reveal the antibacterial effect of honey against EscheriÂ¬chia coli by relating it to the Islam knowledge and technology. The characteristic of honey that has antibacterial activity, is known as the effect of â€œinhibition â€. The antibacterial avtivity is related to total composition of honey, i.e. high sugar concentration, acidity and the presence of pollen. It is also influenced by a substance like lysozyme, which is more commomly known as inhibine. The antibacterial activity of honey is also related to its osmotic process.. Honey is a saturation liquid and supersaturation of sugar which was said to possess osmotic capability. Water molecule reacts strongly to sugar in honey, leaving only a little water to the microorganism â€™s life. DecomposiÂ¬tion of hidrogen peroxide increases reactive-free radical molecules that will react to bacteria and kill it. Osmotic pressure causes hidration of bacteria which hence can not survive.Allah Azza Wa Jalla berfirman dalam Al Qurâ€™an,